Pengaruh Kepercayaan Dan Kualitas Produk Terhadap Minat Beli Sepeda Motor (Studi Kasus Yamaha NMAX Di Kota Bima) - zulfikar, muhammad (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of trust and product quality on the population's buying interest in motorcycles and the sample of this research is to use the unknowns population formula whose population is not known to determine the sample. The number of samples in this study was 96.04 or rounded up to 96 respondents. according to the established criteria. The result of this study is that partially trust has a significant effect on consumers buying Yamaha NMAX motorcycles in Bima city. Simultaneously or simultaneously trust and product quality have a significant influence on interest in buying Yamaha NMAX motorcycles in Bima city. The correlation value (R) generated is 0.910. So it can be concluded that there is a very strong relationship between the independent variable and the dependent variable. While the value of R Square is 0.824. This shows that the trust variable and overall product quality have an influence of 82.4% on buying interest, while the remaining 17.6% is influenced by other variables not examined in this study